2013
DOI: 10.1002/14651858.cd005133.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Pre-emptive treatment for cytomegalovirus viraemia to prevent cytomegalovirus disease in solid organ transplant recipients

Abstract: Pre-emptive treatment for cytomegalovirus viraemia to prevent cytomegalovirus disease in solid organ transplant recipients (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 126 publications
0
63
0
2
Order By: Relevance
“…Preemptive CMV treatment, without the employment of specific CMV prophylaxis is an accepted strategy for minimizing the effects of infection and is employed for lower risk patients or when prophylaxis is not affordable . Relevant clinical endpoints are similar to those obtained with prophylaxis, except for CMV replication rates . However, as a result of permissive CMV replication using this strategy, late infections tend to be rare and very little is known about its clinical course.…”
Section: Discussionmentioning
confidence: 69%
“…Preemptive CMV treatment, without the employment of specific CMV prophylaxis is an accepted strategy for minimizing the effects of infection and is employed for lower risk patients or when prophylaxis is not affordable . Relevant clinical endpoints are similar to those obtained with prophylaxis, except for CMV replication rates . However, as a result of permissive CMV replication using this strategy, late infections tend to be rare and very little is known about its clinical course.…”
Section: Discussionmentioning
confidence: 69%
“…13,14 Efficacy of ganciclovir has been clearly demonstrated across all solid organ transplantation, by preventing CMV infection and disease and by improving survival. Two recent comprehensive systematic reviews 15,16 found that ganciclovir prophylaxis is superior to 17 18,19 .…”
Section: (Val) Ganciclovirmentioning
confidence: 99%
“…[88][89][90] In seropositive heart recipients, both approaches appear to be effective for prevention of the direct effects of acute CMV infection (i.e. CMV syndrome or CMV disease), 15 Effective pre-emptive approach needs an experienced virology laboratory with short turnaround times to process frequent assays, intensive cross-talking between clinicians and laboratory professionals, and strict patient adherence to scheduled blood/tissue sampling. In this setting, historical methods such as shell vial assay or pp65 antigenemia should be replaced by blood polymerase chain reaction (PCR) [96][97][98][99] .…”
Section: Targets and Strategies In Anti-cmv Therapy: Prophylaxis Vs mentioning
confidence: 99%
“…The incidence of CMV infection has been reported to decrease in patients treated with mammalian target of rapamycin–targeting drugs . On the other hand, posttransplant surveillance of viremia in CMV+ KTR allows early detection of viral replication and administration of preemptive therapy …”
Section: Introductionmentioning
confidence: 99%